2003
DOI: 10.2165/00044011-200323080-00005
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polycystic Ovaries with the Use of Valproic Acid in Jordanian Epileptic Patients

Abstract: These results suggest an association between the use of VPA and PCO, hyperandrogenism, obesity and menstrual abnormalities. For women receiving VPA therapy, clinicians should consider performing an assessment of ovarian structure and function, especially if these patients develop menstrual cycle disturbances during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In Jordan, It is found that valproic acid was associated with polycystic ovarian syndrome among epileptic patients [18]. It is reported that UGT2B7*2 affected the glucuronidation of valporic acid [8].…”
Section: Discussionmentioning
confidence: 99%
“…In Jordan, It is found that valproic acid was associated with polycystic ovarian syndrome among epileptic patients [18]. It is reported that UGT2B7*2 affected the glucuronidation of valporic acid [8].…”
Section: Discussionmentioning
confidence: 99%